2009
DOI: 10.1210/jc.2008-1542
|View full text |Cite
|
Sign up to set email alerts
|

Late-Night Salivary Cortisol for Diagnosis of Overt and Subclinical Cushing’s Syndrome in Hospitalized and Ambulatory Patients

Abstract: Our data validate the outpatient bed sampling strategy for NSC with no need for specific outpatient threshold. NSC may be helpful to detect mild recurrence of Cushing's disease after surgery but is of little value in identifying SCSA amongst adrenal incidentalomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 41 publications
8
87
1
5
Order By: Relevance
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As reported in some studies (2,5,6,7,10,11,12,14), we found that LNSC levels were higher in CS; a threshold value above 5.24 ng/ml provided a good accuracy to detect endogenous hypercortisolism, and in particular to discover CD, the most common form. LNSC was able to differentiate CS patients from the control population, which included not only healthy subjects but also patients with suspected CS, and our proposed threshold value is consistent with other data reported in the literature and obtained with RIAs (5, 11, 23).…”
Section: Discussionsupporting
confidence: 77%
“…UFC collection and the 1 mg DST are simple, but neither is able to make a certain diagnosis of CS (15,20,21). The LNSC test, as proposed recently (5,6,7,10,11,12,14), is a reliable, noninvasive, stress-free, and low-cost procedure to diagnose CS. Moreover, elevation of LNSC levels might be the first abnormality to be checked in the follow-up after surgery (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low sensitivity (22.7%), but high specificity (87.7%) for cut-off 0.18 μg/ dL characterised LSC in the study by Masserini et al [20]. In the analysis of Nunes et al, sensitivity and specificity were comparable (77% and 69% respectively) for 0.17 μg/dL [21]. By contrast, Yuko Tateishi et al indicated 0.11 μg/dL value of LSC with 100% sensitivity but only 50% specificity [22].…”
Section: Discussionmentioning
confidence: 85%
“…As an alternative, late-night salivary cortisol can be used, but it has shown less sensitivity when compared to the low-dose dexamethasone suppression test in this subgroup of patients (57,(110)(111)(112)(113). Finally, with regard to first-line methods, 24-h UFC is the method with the highest number of false negative results, as it is diagnostic only when the disease is overt.…”
Section: Adrenal Incidentalomamentioning
confidence: 99%